Role of aldo‐keto reductase family 1 member B1 (AKR1B1) in the cancer process and its therapeutic potential - Khayami, Reza; Hashemi, Seyyed Reza; Kerachian, Mohammad Amin (Journal of cellular and molecular medicine, 2020)
The role of aldo‐keto reductase family 1 member B1 (AKR1B1) in cancer is not totally clear but growing evidence is suggesting to have a great impact on cancer progression. AKR1B1 could participate in a complicated network of signalling pathways, proteins and miRNAs such as mir‐21 mediating mechanisms like inflammatory responses, cell cycle, epithelial to mesenchymal transition, cell survival and apoptosis. AKR1B1 has been shown to be mostly overexpressed in cancer. This overexpression has been associated with inflammatory mediators including nuclear factor kappa‐light‐chain‐enhancer of activated B cells (NFκB), cell cycle mediators such as cyclins and cyclin‐dependent kinases (CDKs), survival proteins and pathways like mammalian target of rapamycin (mTOR) and protein kinase B (PKB) or AKT, and other regulatory factors in response to reactive oxygen species (ROS) and prostaglandin synthesis. In addition, inhibition of AKR1B1 has been shown to mostly have anti‐cancer effects. Several studies have also suggested that AKR1B1 inhibition as an adjuvant therapy could render tumour cells more sensitive to anti‐cancer therapy or alleviate the adverse effects of therapy. AKR1B1 could also be considered as a potential cancer diagnostic biomarker since its promoter has shown high levels of methylation. Although pre‐clinical investigations on the role of AKR1B1 in cancer and the application of its inhibitors have shown promising results, the lack of clinical studies on AKR1B1 inhibitors has hampered the use of these drugs to treat cancer. Thus, there is a need to conduct more clinical studies on the application of AKR1B1 inhibitors as adjuvant therapy on different cancers.